Relationship Between Stress and Deformation of Frozen Soils Taking Into Account the Time Factor - Vyalov,S. S. (1970)
In order to study the relationship between stress and deformation of frozen soils, experiments were made on displacement along wooden rods which were frozen into the ground, on the penetration into frozen soils of hard indenters, and on tension and compression. The experiments were conducted with various types of soils (from clays to light-weight sandy slits), at various sub-zero temperatures, which were always constant for any given experiment. In order to show the effect of time, experiments conducted were both short-term and very lengthy (lasting several months and even more than a year). (Author) Trans. of Akademiya Nauk SSSR. Doklady, v108 n6 p1049-1052 1956.